The role of stress echocardiography in identifying cardiotoxicity: an in-depth exploration - Wang, Sijia; Wang, Yi; Wang, Shuang (Frontiers in Cardiovascular Medicine, 2024)
Cancer treatment might cause heart failure and deteriorate the patients' quality of life. Despite the wide use of conventional echocardiography, it often fails to detect cardiotoxicity until advanced cardiac dysfunction at potentially irreversible stages. Advanced techniques, such as three-dimensional imaging and strain analysis in stress echocardiography, have shown promise in identifying cardiotoxicity at subclinical stages, even when traditional measures remain within normal ranges. These novel techniques have been shown to identify cardiac impairment in 30-50% of the patients undergoing potentially cardiotoxic chemotherapy, which allows for early intervention and enhanced patient management. Although professional societies are advocating for the inclusion of these techniques into routine monitoring protocols, more research is needed to optimize and standardize their use across various centers and chemotherapeutic agents. This review explores the role of stress echocardiography in the early detection and monitoring of chemotherapy-induced cardiotoxicity. It delves into current knowledge and emerging research, aiming to provide a comprehensive understanding and to highlight areas worthy of further investigation.